Purchase order for supply, installation & commissioning of MS grating for Brac University new campus project at holding no. Kha-224, Merul Badda, Dhaka-1212 (Brac University, 2023)
This purchase order has been made between Brac University and MR Corporation for supply, installation & commissioning of MS grating for Brac University new campus project.